The SARS-CoV-2 differential genomic adaptation in response to varying UVindex reveals potential genomic resources for better COVID-19 diagnosis and prevention - Iqbal, Naveed; Rafiq, Muhammad; Masooma,; Tareen, Sanaullah; Ahmad, Maqsood; Nawaz, Faheem; Khan, Sumair; Riaz, Rida; Yang, Ting; Fatima, Ambrin; Jamal, Muhsin; Mansoor, Shahid; et al. (Frontiers in Microbiology, 2022)
Abstract The COVID-19 has been a pandemic disease reported almost from every country and causes life threatening sever respiratory symptoms. Recent studies showed, various environmental selection-pressures challenge the severe-acute-respiratory-syndrome-coronavirus-2 (SARS-CoV-2) infectivity, and in response, the virus engenders new mutations leading to the emergence of more virulent strains of WHO concern. Advance prediction of the forthcoming virulent SARS-CoV-2 strains in response to the principal environmental selection-pressures like temperature, and solar UV radiation is indispensable to overcome COVID-19. To discover the UV-solar radiation-driven genomic adaption of SARS-CoV-2, a curated data set of 2,500 full-grade genome from five different UVindex regions (25-countries) was subjected to in-depth downstream genome-wide analysis. The recurrent variants that best respond to UV-solar radiations were extracted and extensively annotated to determine their possible effects and impacts on genes functions. This study revealed 515 recurrent single nucleotide variants (rcntSNVs) as SARS-CoV-2 genomic responses to UV-solar radiation, of which 380 were found distinct. For all discovered rcntSNVs, 596 functional effects (rcntEffs) were detected, containing 290 missense, 194 synonymous, 81 regulatory, and 31 in intergenic region. The highest counts of missense rcntSNVs in Spike (27) and Nucleocapsid (26) genes explain the SARS-CoV-2 genomic adjustment to escape immunity and prevent UV-induced DNA damaging effect, respectively. Among all, the most commonly observed rcntEffs were four missense (RdRp-Pro327Leu; N-Arg203Lys; N-Gly204Arg; Spike-Asp614Gly) and one synonymous (ORF1ab-Phe924Phe) functional effects. The highest number of rcntSNVs were distinct and were uniquly attributed to specific UVindex-regions, proposing solar-UV radiation as one of the driving forces for SARS-CoV-2 differential genomic adaptation. The phylogenetic relationship indicated the High UVindex-region populating SARS-CoV-2 as the recent progenitor of all included samples. Altogether these results provide baseline genomic data that may need to be included for preparing UVindex region specific future diagnostic and vaccine formulations.